Hubungan Persepsi Mahasiswa pada E-Module Materi Cermin Cekung dengan Keterampilan Proses Sains Dasar - Neng Ria Nasih; Syahriadi Sinaga (SAP (Susunan Artikel Pendidikan), 2019)
Perceptions held by students differ depending on what is being observed by students. In the modern era, it can utilize technology as a medium for learning and assessment. In line with the 4.0 revolution which almost all have used technology. With this research aims to see the relationship between students 'perceptions with students' basic science process skills in concave mirror material by utilizing technology in their learning. The method used in this study is a quantitative associative research method with a correlational research design. The research technique used was purposive sampling technique. The results of the data that have been analyzed produce that the basic science process skills of students towards the use of concave mirror material e-modules produce a percentage of 41.2% with a very good category and the students' perception of the use of concave mirror material e-modules is 61.8% with very good categories. Based on the significance value generated, it can be said that the relationship on students 'basic science process skills with the students' perception of the use of concave mirror material e-modules is very strong with the Pearson correlation of 0.958 and a significance of 0.000.